An Exact Estimate for the Measure of the Exceptional Set in the Borel Relation for Entire Functions - Filevych, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain an exact estimate for the measure of the exceptional set in the Borel relation for entire functions.